A new species of Tephritis Latreille (Diptera: Tephritidae) with an unusual wing pattern from Iran and its taxonomic implications - Khaghaninia, Samad; Zarghani, Ebrahim; Namin, Saeed Mohamadzade; Korneyev, Valery A. (Zootaxa, 2011)
Tephritis sahandi new species from Iran (type locality: Sahand chain mountains, East Azerbaijan Province) with an uncommon banded wing pattern is described and shown to be related to Pangasella volkovitshi Richter from Tadjikistan. Both species fit the diagnosis of the genus Tephritis Latreille 1804, and possess its key characters; as the result, Pangasella Richter 1995 (type species: Pangasella volkovitshi Richter 1995) is shown to be a new junior synonym of Tephritis, and its type species is transferred to the genus as Tephritis volkovitshi (Richter 1995) new combination. A key to the Palaearctic species of banded-winged Tephritis is provided.